2014
DOI: 10.1103/physrevlett.113.057601
|View full text |Cite
|
Sign up to set email alerts
|

Spin Pumping and Spin-Transfer Torques in Antiferromagnets

Abstract: Spin pumping and spin-transfer torques are two reciprocal phenomena widely studied in ferromagnetic materials. However, pumping from antiferromagnets and its relation to current-induced torques have not been explored. By calculating how electrons scatter off a normal metal-antiferromagnetic interface, we derive pumped spin and staggered spin currents in terms of the staggered field, the magnetization, and their rates of change. For both compensated and uncompensated interfaces, spin pumping is of a similar mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
427
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 390 publications
(438 citation statements)
references
References 40 publications
11
427
0
Order By: Relevance
“…Unlike the treatment of Ref. [20], in NiO, there are two significant anisotropies to consider. As a starting point in the exploration of high-frequency spintronics, it is also important to tune the resonance frequencies to a lower gigahertz range for easier detection by conventional electronics.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike the treatment of Ref. [20], in NiO, there are two significant anisotropies to consider. As a starting point in the exploration of high-frequency spintronics, it is also important to tune the resonance frequencies to a lower gigahertz range for easier detection by conventional electronics.…”
mentioning
confidence: 99%
“…Our main findings are that, when applying an external magnetic field along the easy axis close to the spin-flop transition, we can decrease the resonance frequency while simultaneously significantly increasing the inverse spin Hall signal. The increase in the signal can even overcome the previously anticipated limiting factor in antiferromagnet spin pumping: the ratio of the anisotropic energy to the exchange energy [20].We consider a small antiferromagnet in the macrospin limit whereby all spin excitations are homogeneous. The antiferromagnet has two sublattices, with temporal magnetizations M 1 and M 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18 It was recently reported that spin pumping exists also at the interface of AFM/normal metal. 25 In fact, AFM layer may even enhance the spin pumping. Thus, electrical detection of the coupling signal in AFM is also possible in the hybridized structures.…”
mentioning
confidence: 99%